Kedudukan Otoritas Jasa Keuangan Pada Perusahaan Modal Ventura Asing - Anak Agung Sagung Ngurah Indradewi (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
The juridical basis for supervision of foreign venture capital companies is contained in the provisions of Capital Law No. 21 of 2008 concerning the Financial Services Authority (OJK), Presidential Regulation No. 9 of 2009 concerning Financing Institutions and Minister of Finance Regulation No. 18 / PMK.010 / 2012 concerning Venture Capital Companies. Foreign venture capital companies that invest directly in Indonesia are a form of foreign investment. This is inseparable from the wide scope of foreign capital, which is defined as capital owned by foreign countries, individual foreign citizens, foreign business entities, foreign legal entities, and / or Indonesian legal entities whose capital is partly or wholly owned by foreign parties. Supervision of foreign investment is carried out by the Investment Coordinating Board in accordance with the provisions of Law No. 25 of 2007 concerning Investment. In accordance with the provisions in Permenkeu No. 18 / PMK / 0.10 / 2012 explained that the scope of supervision of venture capital carried out by the OJK is only limited to PMV Indonesia (Cooperatives or Limited Liability Companies). The implication is that OJK cannot supervise foreign PMVs that carry out direct financing. Because financing activities by foreign venture capital companies have intersecting rules, it is appropriate that foreign venture capital regulations only follow one specific rule. The regulation regarding financing institutions is only regulated in a Presidential Regulation. Although hierarchically, the status of the Perpres is an implementing regulation of the Law, the substance it regulates is not identical with the provisions of the Law which mandates it. Therefore, the provisions regarding financing activities should be regulated in a separate Law